PENGARUH PEMBERIAN LIDAH BUAYA (Aloe vera) TERHADAP STAMINA ATLET BKMF PENCAK SILAT - Sevita Anggi Primadani; Sarifin G; Ichsani Ichsani (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
This study aims to determine the effect of aloe vera on the stamina of BKMF martial arts. This type of research is a quasi-experimental design with one group pre-test and post-test.Total sample of 10 athletes and sampling using random sampling. The data analysis techniques used were Descriptive Test, Data Normality Test, and T Test. Based on data analysis, the results of descriptive tests with athlete stamina data before administration of aloe vera obtained an average value (mean) 31.14, standard deviation 1.93, minimum value 29.10, maximum value 33.60. Athletes' stamina data after administration of aloe vera obtained an average value (mean) of 37.41, standard deviation of 1.06, minimum value of 35.70, maximum value of 38.50. The results of the normality test of the athlete's stamina data before giving aloe vera obtained the Kolmogorov Smirnov value of 0.64, Asmp = 0.80 (P > 0.05). Stamina data after administration of aloe vera obtained Kolmogorov smirnov value of 0.80, Asmp = 0.53 (P > 0.05). The results of the t-test of data analysis obtained a value of sig 0.00 (sig < 0.05), with a difference of 6.27 which means that there is an effect of giving aloe vera on the stamina of BKMF martial arts athletes